Critical secrets: tensions between authoring texts and the readability of leveled books - Tiffany L. Gallagher; Kari-Lynn Winters (Educational Role of Language Journal, 2020)
In this inquiry an educational researcher and children’s book author interrogated the process of the authorship of leveled readers, reconciling publishing protocols and readability formulae in order to encourage critical viewpoints for readers and educators. Data included publishers’ guidelines, interviews, journaled field notes, readability scores, and draft samples of leveled book manuscripts. Qualitative analyses yielded three themes that offer a glimpse into the tensions that a leveled text author contemplates prior to and during the writing process. Issues of engagement, power, identity and agency are peppered throughout the author’s process. Finally, there is a discussion of the impact of text readability calculations. This paper brings to light critical questions that educators and administrators might ask about leveled text readability in relation to their students’ needs and considerations for educators to bring a critical literacy approach into the classroom during the use of leveled texts.